2017
DOI: 10.1016/j.cobme.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

A network neuroscience of neurofeedback for clinical translation

Abstract: In the emerging field of network neuroscience, the brain is represented as a network of discrete yet functionally and structurally interconnected areas. Mathematical and computational tools to characterize the organization of this network can provide insights into the principles guiding brain structure and function, and can pinpoint differences between healthy individuals and individuals suffering from psychiatric disease or neurological disorders. The field is now faced with the question of how to devise clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Specifically, assuming a model of brain dynamics allows us to determine which nodes could most easily drive transitions in the state of brain activity via some stimulatory input. The network control theory that we use here to study the internal modulation of brain state (via undertaking a task requiring executive function) also makes explicit predictions about the external modulation of brain state (via stimulation or neurofeedback) 62 . Indeed, average controllability values were associated with sex-dependent, symmetric patterns of brain activity ( Fig.…”
Section: Implications For Cognitive and Clinical Neurosciencementioning
confidence: 99%
“…Specifically, assuming a model of brain dynamics allows us to determine which nodes could most easily drive transitions in the state of brain activity via some stimulatory input. The network control theory that we use here to study the internal modulation of brain state (via undertaking a task requiring executive function) also makes explicit predictions about the external modulation of brain state (via stimulation or neurofeedback) 62 . Indeed, average controllability values were associated with sex-dependent, symmetric patterns of brain activity ( Fig.…”
Section: Implications For Cognitive and Clinical Neurosciencementioning
confidence: 99%
“…27 Given that the efficacy of the established pharmacological and behavioral treatment options for these disorders is limited, 28 it has been advocated to employ hemodynamic imaging-informed NF to modulate the identified neural alterations in a regionalspecific manner to alleviate psychiatric symptoms and normalize functional deficits. [28][29][30][31] To facilitate translation of hemodynamic NF into clinical applications, the present randomized, sham-controlled study aims at evaluating the feasibility to employ fNIRS-informed NF as strategy to modulate brain activity. Initial studies have demonstrated the feasibility to use fNIRS-informed NF to allow participants to acquire regulatory control over brain activity in motor-related regions.…”
Section: Introductionmentioning
confidence: 99%
“…In the first study of its kind, applying an integrated IEEG-fMRI method, we have shown that established markers of memory encoding correspond to meaningful network differences captured by rsfMRI. In clinical terms, knowing a region is a hub, playing an important role in multi-regional and multi-functional connectivity, may inform technologies trying to identify the most effective targets to electrically or pharmacologically stimulate for cognitive enhancement in areas such as memory Ezzyat Y et al, 2018;Kucewicz MT et al, 2018), or perhaps be used to identify the areas with sufficient influence over targets to generate effective neuro-feedback loops (Hohenfeld C et al, 2017;Murphy AC et al, 2017).…”
Section: Discussionmentioning
confidence: 99%